Behaviour of macro-synthetic fibers reinforced concrete: Experimental, numerical and design code investigations. (August 2021) - Nana, W.S.A.; Tran, H.V.; Goubin, T.; Kubisztal, G.; Bennani, A.; Bui, T.T.; Cardia, G.; Limam, A.
Abstract: Fiber-reinforced concrete (FRC) is increasingly used in various civil engineering applications. Compared to conventional reinforced concrete (rebars or welded mesh), the FRC has very high ductility in the post-cracking phase and allows more distributed cracks with a smaller opening. The FRC post-cracking behaviour depends on the fiber type (properties of fibers) used and the fiber content. Therefore, the characterization of fiber-reinforced concrete material behaviour under tension is important. In this study, the post-peak behaviour of the FRC using polypropylene macro-synthetic fiber (SikaFiber Force-60 brand) was characterized. According to the European test recommendation (EN 14651, 2005), notched 3‐point bending tests were conducted on 36 prismatic notched beams (dimensions of 600 mm × 150 mm × 150 mm) to identify the stress/crack opening law of FRC. The influence of the fiber dosage was evaluated with six fiber volume fractions of 0.33%, 0.49%, 0.66%, 0.82%, 0.99% and 1.26% corresponding to dosages of 3.0 kg/m 3, 4.5 kg/m 3, 6.0 kg/m 3, 7.5 kg/m 3, 9.0 kg/m 3 and 11.5 kg/m 3 respectively. It was found that the increase of the fiber dosage has no significant influence on the ultimate bending strength, but a substantial increase in the residual tensile flexural stresses was found. A numerical model using the inverse method was also used to reproduce the stress/crack opening behaviour of FRC obtained in the experimental tests. A new approach was proposed to define the post-cracking diagram adapted for the macro-synthetic FRC used. Fib Model Code 2020 approach was also conducted and compared with. The Model Code requirements for FRC's use in structural applications have also been adapted to the case of macro-synthetic FRC following Hillerborg's concept of fracture energy and a new proposal was made.